Unemployment in Europe and the United States under COVID-19: Better constrained in the corset of an insurance logic or at the whim of a liberal presidential system? - Georg Fischer; Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
The effects that the economic crisis triggered by COVID-19 is having on unemployment could hardly differ more than in the United States and Europe. This divergence also applies to the political reactions to it. Whereas the 27 member states of the European Union (EU-27) managed to keep unemployment in check largely through heavy reliance on short-time work or similar measures, the United States has been experiencing mass unemploy-ment reminiscent of the Great Depression of 1929/1930. Instead of short-time work, the United States has resorted partly to massive social transfers for certain groups of the unemployed, which may temporarily even raise some incomes to levels above those offered by employment. However, the social problems and the limits of economic policy associated with short-time work in the EU-27 are becoming increasingly apparent and unemployment is rising steadily, in particular among vulnerable groups. It is not yet clear which of these two economic and social systems will cope better in the long term with the industrial transformation that the crisis is accelerating. This essay argues that the European approach promises a more humane and effective solution to the crisis, but only if the European Union and its member states find a way to combine short-time work with more forward-looking labor market and social policies. It suggests that they could learn from some of the strengths of the U.S. system to improve the interaction between the federal government and the states. – – Die Auswirkungen der von COVID-19 ausgelösten Wirtschaftskrise auf die Arbeitslosigkeit könnten kaum unterschiedlicher sein als in den USA und Europa. Das gilt auch für die politischen Reaktionen: Während die 27 Mitgliedstaaten der Europäische Union (EU-27) die Arbeitslosigkeit bisher weitgehend durch massiven Einsatz von Kurzarbeit oder ähnlichen Maßnahmen in Schach halten konnte, herrschte in den USA zeitweilig eine Massenarbeits-losigkeit, die an die Große Weltwirtschaftskrise 1929/1930 erinnerte. Statt mit Kurzarbeit reagierten die USA u.a. mit massiven Sozialtransfers für bestimmte Gruppen von Arbeits-losen, die manche Einkommen kurzfristig sogar besserstellen als bei Beschäftigung. Um-gekehrt werden die sozialen Probleme und die wirtschaftspolitischen Grenzen der Kurz-arbeit in der EU deutlich sichtbar, und die Arbeitslosigkeit steigt zunehmend, insbeson-dere für benachteiligte Gruppen auf dem Arbeitsmarkt. Es ist also noch nicht ausgemacht, welches dieser beiden Wirtschafts- und Sozialsysteme langfristig den durch die Krise beschleunigten Strukturwandel besser bewältigen wird. Dieser Essay argumentiert, dass der europäische Ansatz eine humanere und effektivere Lösung der Krisenbewältigung verspricht, aber nur, wenn die EU und ihre Mitgliedstaaten einen Weg finden, die Kurz-arbeit mit mehr vorausschauender Arbeitsmarkt- und Sozialpolitik zu kombinieren und von einigen Stärken des US-Systems hinsichtlich der Interaktion zwischen Föderation und Einzelstaaten zu lernen.
Keywords: 300; Unemployment; short-time work; structural change; risk-sharing; USA; Europe; COVID-19; Arbeitslosigkeit; Kurzarbeit; Strukturwandel; Risikoteilung; USA; Europa